2017
DOI: 10.1007/978-3-319-58904-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Abelian Gauge Potentials on Cubic Lattices

Abstract: The study of the dynamics of a quantum particle in a magnetic field is a fascinating subject of perduring interest both in physics and mathematics literature. The quantization of energy levels giving rise to the Landau levels is at the basis of our understanding of integer and fractional quantum Hall effects [1, 2, 3, 4, 5] and its higher-dimensional counterparts and generalizations, including topological insulators [6,7,8]. The use of vector potentials in quantum mechanics is associated in itself to very inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 76 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…In both cases, suitable pairs of Raman lasers allow us to engineer an effective long-time dynamics of the system described by a low-energy tight-binding Hamiltonian characterized by position-dependent phases in the hopping amplitudes of the atoms (see, for example, Refs. [46][47][48][49]). The resulting artificial gauge flux χ in each plaquette depends on the recoil momentum of the Raman lasers and can be varied by tuning the angle between them (see, for example, the experiments [50][51][52]).…”
Section: The Modelmentioning
confidence: 99%
“…In both cases, suitable pairs of Raman lasers allow us to engineer an effective long-time dynamics of the system described by a low-energy tight-binding Hamiltonian characterized by position-dependent phases in the hopping amplitudes of the atoms (see, for example, Refs. [46][47][48][49]). The resulting artificial gauge flux χ in each plaquette depends on the recoil momentum of the Raman lasers and can be varied by tuning the angle between them (see, for example, the experiments [50][51][52]).…”
Section: The Modelmentioning
confidence: 99%
“…In Section 3, several examples of techniques to engineer complex phases on the hopping parameters are discussed. Reviews can be found in [21][22][23][24].…”
Section: Static Fieldsmentioning
confidence: 99%
“…, L − 1. The Hamiltonian (2) is then finally rewritten in the above defined MBZ and in the basis of the n s sublattices as in equation (17), and three n s × n s matrices are derived similarly to what has beed done in the previous section for the three matrices T AB ĵ in equation (18). Similar results can be obtained using a different optimal gauge choice through the mapping onto a onedimensional model in momentum space [38].…”
Section: Anisotropic Abelian Lattice Fluxesmentioning
confidence: 99%
“…(36) has the same symmetries of the one in Eq. (17). As a consequence, its spectrum divides in 2n generally non-degenerate subbands.…”
Section: Translationally Invariant Non-abelian Gauge Potentialsmentioning
confidence: 99%
See 1 more Smart Citation